Experience of the San Pablo Hospital Complex (Peru) in the implementation of an electronic medical records system - Huapaya-Huertas, Oscar (2022)
In Peru, the vast majority of health facilities, both public and private, still have medical record formats on paper. Migration to the electronic health records information system (SIHCE) has been seen to be a great challenge in many respects. The San Pablo Hospital Complex (CHSP) is made up of eleven health establishments distributed in four departments of the country. In this article we report the process of implementing the SIHCE in the CHSP through the software circuit, for which the following steps were followed: 1) Decision to implement an EHR system, 2) Constitution of the committee, 3) Benchmarking and evaluation 4) Implementation plan, 5) Coordination meetings, 6) Testing, 7) Trainings, 8) Go Live, and 9) Implementation by replication. Likewise, we reflect on the lessons learned during this process, which revolve around two angles: management versus change and process modifications. The experience presented in this paper could be of use to other healthcare providers that wish or are in the process of implementing an SIHCE system in a context similar to ours.